Chirurgia ortopedica in regime di day-surgery. Valutazione del dolore post-operatorio con buprenorfina, ossicodone e idromorfone - Orthopaedic surgery in a day-surgery setting. Comparing postoperative pain relief obtained with buprenorphine, oxycodone and hydromorphone - Elisabetta Ercolani; Vitalba Vitale; Nicolino Monachese; Daniele Battelli; Pierluigi Arcangeli (Publiediting, 2010)
In a day-surgery setting, the use of protocols for post-operative analgesia is strongly reccomended, such as the patient caring done by nurses: this is because the patient leaves the hospital during the development of the postoperative problems that should be treated even when he's came back home. Doing this, an important step is to take into the operating theatre a ell-educated patient, about the surgical event, its complications and its risks. The administration route of the analgesic drugs must be oral or transcutaneous. It's truly important, for us, to have well studied protocols, but a truly important role is played by the nurse caring, that should embrace the patient from the surgical preparation to the fi rst days immediately after discharge. This study compares effi cacy and adverse effects of three post-operative analgesia protocols, using hydromorphone, oxycodone and buprenorphine, associated with a patient counselling done by nurses.